Universal Trap Effect in Carrier Transport of Disordered Organic Semiconductors: Transition from Shallow Trapping to Deep Trapping - Li, Chen; Duan, Lian; Li, Haoyuan; Qiu, Yong (Journal of physical chemistry. C, 2014)
In order to unravel the effect of trap energy on carrier transport in disordered organic semiconductors, a comprehensive study was conducted on hole transport in a series of organic molecular hosts with explicit traps at different trap energies. The mobility measured by time-of-flight experiments was found to decrease significantly at shallow trapping, but hardly decreased at deep trapping, where a sharp decrease of carrier density was observed. By analyzing temperature dependence of the mobility, the decreased mobility at shallow trapping were found to originate from increased energetic disorder and activation energy, whereas both energetic disorder and activation energy are changeless at deep trapping. We find it reasonable to cover the different effects of deep trapping and shallow trapping in a universal mechanism based on the Miller–Abrahams hopping model, and carry out multiple-carrier Monte Carlo simulations to elaborate how, within a universal mechanism, that deep and shallow traps affect energetic disorder, transporting trajectories and carrier density in different ways. The results suggest transporting at shallow trapping always is involved in a multiple-trapping-release process owing to frequent thermal reactivation, thus leading to winding transporting trajectory, increased effective energetic disorder, and increased activation energy; while deep traps tend to immobilize the carriers and act as ionized scattering centers, thus mainly decreasing the carrier density and just elongating the trajectory slightly. Investigating the change of mobility with continuous trap energy suggests a transition region, rather than a strict borderline existing between deep traps and shallow traps, where carrier transport is controlled by both deep traps and thermal reactivation from shallow traps.